Advancing ESG Reporting and Assurance in the Accounting Profession for Enhanced Sustainability - Happy, Babrah; Nyombi, Amos; Sekinobe, Mark; Ampe, Jimmy; Nagalila, Wycliff (International Journal of Research in Interdisciplinary Studies, 2024)
This review paper explores the transformative role of Environmental, Social, and Governance (ESG) reporting and assurance within the accounting profession to foster sustainable business practices and meet the growing demands from investors, regulators, and consumers. It examines the effectiveness of current accounting practices in integrating ESG factors, evaluates the benefits and challenges associated with ESG reporting and assurance, and explores the potential impacts on corporate transparency and sustainability. The study reveals significant benefits in enhancing corporate accountability and promoting sustainable practices while highlighting the challenges of implementing these processes to ensure accuracy and reliability. Policy recommendations include promoting professional certification, developing standardized reporting practices, and enhancing regulatory frameworks to support the accounting profession in advancing ESG practices. Future research should focus on developing innovative tools for ESG reporting and assurance to address identified gaps and support global sustainability efforts.